If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 3) = 2(3x + 1) + 16 Reorder the terms: 6(3 + x) = 2(3x + 1) + 16 (3 * 6 + x * 6) = 2(3x + 1) + 16 (18 + 6x) = 2(3x + 1) + 16 Reorder the terms: 18 + 6x = 2(1 + 3x) + 16 18 + 6x = (1 * 2 + 3x * 2) + 16 18 + 6x = (2 + 6x) + 16 Reorder the terms: 18 + 6x = 2 + 16 + 6x Combine like terms: 2 + 16 = 18 18 + 6x = 18 + 6x Add '-18' to each side of the equation. 18 + -18 + 6x = 18 + -18 + 6x Combine like terms: 18 + -18 = 0 0 + 6x = 18 + -18 + 6x 6x = 18 + -18 + 6x Combine like terms: 18 + -18 = 0 6x = 0 + 6x 6x = 6x Add '-6x' to each side of the equation. 6x + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| u-3/4=7(3/5) | | 9-18+8= | | (v+4)(v-8)= | | -3x+6x+8= | | 164-w=250 | | -3+6(-3)+8= | | 3x+5=12y | | Y^3-9y^2+8y=0 | | 2x^2-14x-32=0 | | 5(Y-3)/3 | | 81=8x-7 | | (2x+3)(2x^2-15x+28)=0 | | 14+9x=50 | | 5=5x-10 | | -8x=-111+15 | | 63=8x-9 | | 5(y-3)/3=-3y | | 15+4x=43 | | 5x-5=75 | | x^2+1/10x+1/50=0 | | 9(5g+2)=54 | | -x^2-14x+240=0 | | 80=8x+20y | | 5d+3=2d+18 | | 9(x-5)=27.9 | | 4.4+10y=40 | | 6(a+5)=36.6 | | 6.4=2c-5 | | 2e-2=17 | | 9x+25=13 | | %increase13066over12610 | | 9(x-7)=-18 |